Analyzing the Extent of Inequality in the Time Uptake of Postgraduate users of Central Library: A Gender Study - Saravanan, T; Gana, GS (Journal of Advanced Research in Library and Information Science, 2021)
In this paper we have applied the Quantile technique to analyze the inequality in the time consumption of Postgraduate students belonging to 4 disciplines of Annamalai University. The disciplines Chemistry, Computer Science, Maths and Physics were classified according to the pattern of user’s time consumption level in the Library across gender. A Quantile technique has been applied to analyze the sample. The Distribution function, Lorenz function, Lorenz Plot (Lorenz M. O. 1905) and Gini Coefficient (Gini C. 1909) were obtained through this technique. The framed research question is; what is the extent of gender inequality in the time consumption? The extracted Gini coefficient values for various disciplines are; Chemistry (male=0.000, female=0.106), Computer Science (male=0.000, female=0.000), Maths (male=0.000, female=0.060) and Physics (male=0.000, female=0.000). Modern Librarians are in need of new techniques to measure the users’ attitudes so as they can admin their Libraries in order to deal the real problems effectively and efficiently (Saravanan T. 2013a & 2017).